Pengaruh Inovasi Hijau, Tanggung Jawab Sosial Perusahaan, dan Pertumbuhan Penjualan terhadap Profitabilitas Perusahaan: Bukti dari Perusahaan-Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia (2020–2024) - Syahda Candraningtias, Ananda; Khairunnisa (Universitas Muhammadiyah Pontianak, 2026)
This study aims to examine the effect of green innovation, corporate social responsibility (CSR), and sales growth on the profitability of energy sector companies listed on the Indonesia Stock Exchange during 2020–2024. Profitability is measured by Return on Assets (ROA), green innovation by PROPER ratings, CSR by the GRI disclosure index, and sales growth by annual sales growth. This study employs a quantitative approach using panel data from nine companies selected through purposive sampling. The data are analyzed using panel data regression. The findings are expected to provide implications for companies and investors in improving profitability through sustainability practices and sales growth.